Incidence of Vacuum Phenomenon Related Intra-articular or Subfascial Gas Found on Computer-Assisted Tomography (CT) Scans of Closed Lower Extremity Fractures. Issue 11 (November 2017) - Noble, Tyler; Romeo, Nicholas M.; LeBrun, Christopher T.; DiPasquale, Thomas
Abstract : Objectives: To determine the incidence of vacuum phenomenon related intra-articular or subfascial gas found on computer-assisted tomography (CT) scans of closed lower extremity fractures. Design: Retrospective Review. Setting: Level I Trauma Center. Patients/Participants: A total of 153 patients with closed lower extremity fractures. Intervention: CT scans of identified individuals were reviewed for the presence or absence of gaseous accumulations. Main Outcome Measurements: The presence or absence of gas on CT. Results: Twenty seven (17.6%) of the 153 fractures were found to have intra-articular or subfascial gas on CT despite clear documentation, indicating a closed injury with no significant skin compromise. Of the intra-articular fractures (OTA/AO 33B/C, 41B/C and 43B/C), 20% (23 of 113) were found to have gas on CT. All cases were associated with fracture of the tibia ( P = 0.002). Conclusions: Computed tomography demonstrated the presence of intra-articular or subfascial gas in 17.6% (27/153) of closed lower extremity fractures and in 20% (23/113) of closed intra-articular fractures. The possibility of vacuum phenomenon must be considered when using this imaging modality as the confirmatory test for open intra-articular fracture or traumatic arthrotomy. Level Of Evidence: Level IV.